Effect of the mixture of mulberry leaf powder and KGM flour on promoting calcium absorption and bone mineral density in vivo. (22nd April 2020) - Deng, Liling; Liu, Dan; Zhang, Qi; Luo, Jinhua; Zhong, Geng
Abstract: BACKGROUND: In this paper, mulberry leaf powder (MLP) and konjac glucomannan (KGM) flour were used as raw materials, and animal experiments were designed to evaluate the effects of a mixture of MLP and KGM on bone density. The femoral bone microstructure of mice and pathological changes were observed by using micro‐computed tomography) and haematoxylin and eosin (HE) staining methods, respectively. A three‐point bending test was used to determine the biomechanical properties of the femur. RESULTS: Results indicated that the calcium content of MLP was high, reaching 16 148.5 mg kg −1, and the total proportion of water‐soluble calcium, calcium pectinate, and calcium carbonate accounted for about 60% of the total calcium content. Serum alkaline phosphatase (AKP) activity was significantly lower, and serum calcium content was significantly higher ( P  < 0.05), in the MLP + KGM group (KM) than in the low‐calcium control group, whereas no significant difference ( P  > 0.05) was found for serum phosphorus content. KM had a longer femur length, a higher bone mineral density (BMD) ( P  > 0.05), and significantly greater femur diameter, dry weight, index and bone calcium content ( P  < 0.05). However, these parameters were not significantly different from those of the calcium carbonate control group ( P  > 0.05). CONCLUSION: The results indicate that the MLP/KGM mixture can reduce the high rate of bone turnover and the corresponding loss of bone mass caused by calcium deficiency and is thus effective in enhancing bone density. © 2019 Society of Chemical Industry